PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DAN MANAGEMENT PROJECT DALAM MENINGKATKAN KUALITAS DAN KINERJA PADA PT. KIMIA FARMA, TBK - Sylvia Sylvia; Reky Martin; Fatimah Febriani (Jurnal Bina Manajemen, 2023)
The quality and performance of a given pharmaceutical company determines the success of competition in meeting patient satisfaction and is one of the important things that determines business development strategy and maintains the quality of the pharmaceutical company itself. Total Quality Management (TQM) is amanagement system used to improve service quality and help achieve targets set by an organization. This research is an observational study using interviews through questionnaires conducted at 40 Kimia Farma pharmacy outlets in Batam with the aim of analyzing the implementation of Total Quality Management in the city of pharmacy services. In determining the development strategy of PT. Kimia Farma Tbk, conducted a Focus Group Discussion (FGD) to analyze the internal and external factors of Kimia Farma with a SWOT analysis. The results of the evaluation carried out by performance analysis showed an average performance value of 4.05 and an average importance value of 4.31 and an average conformity level of all components of 93.87%. So it can be said that the application of Total Quality Management at PT. Kimia Farma Tbk has been running well. The development strategy that can be carried out based on the SWOT analysis is the SO (Strengths-Oportunity) strategy to optimize the available resources and maximizethe success of existing opportunities in order to improve the performance of PT. Kimia Farma Tbk